2010
DOI: 10.1002/etc.386
|View full text |Cite
|
Sign up to set email alerts
|

Environmental contaminant effects on juvenile striped bass in the San Francisco Estuary, California, USA

Abstract: The decline of pelagic organisms in the San Francisco Estuary (SFE) (California, USA) is attributed to several factors, including water diversions, invasive species, and exposure to environmental toxicants. The present study evaluated the effects of environmental contaminants on liver vitellogenin, metallothionein, 7-ethoxyresorufin-O-deethylase (EROD), and benzyloxyresorufin O-deethylase (BROD) activity in juvenile striped bass (Morone saxitilis) in the SFE. Analysis of juvenile striped bass liver extracts re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Liver microsomal 7 ethoxyresorufin-O-deethylase (EROD) activity is commonly used as a proxy of Cyp1a induction. Although Cyp1a is the main enzyme catalyzing the de-ethylation of ethoxyresorufin, other CYP enzymes also can contribute to EROD activity (Spearow et al 2011). It has also repeatedly been reported that EROD can substantially be inhibited by elevated levels of PCBs, fluoranthene (a prevalent PAH), dioxins and heavy metals (e.g., Viarengo et al 1997;Gooch et al 1989;Willett et al 2001;Ortiz-Delgado et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Liver microsomal 7 ethoxyresorufin-O-deethylase (EROD) activity is commonly used as a proxy of Cyp1a induction. Although Cyp1a is the main enzyme catalyzing the de-ethylation of ethoxyresorufin, other CYP enzymes also can contribute to EROD activity (Spearow et al 2011). It has also repeatedly been reported that EROD can substantially be inhibited by elevated levels of PCBs, fluoranthene (a prevalent PAH), dioxins and heavy metals (e.g., Viarengo et al 1997;Gooch et al 1989;Willett et al 2001;Ortiz-Delgado et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It has also repeatedly been reported that EROD can substantially be inhibited by elevated levels of PCBs, fluoranthene (a prevalent PAH), dioxins and heavy metals (e.g., Viarengo et al 1997;Gooch et al 1989;Willett et al 2001;Ortiz-Delgado et al 2008). EROD activity is technically easy to measure, and it is still considered as a robust biomarker (Oris and Roberts 2007); however, this enzymatic activity biomarker shows some limitations that can make interpretation sometimes difficult in field studies (Spearow et al 2011). Although several studies have focused separately on Cyp1a induction at different organizational levels such as gene expression (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Organisms can also acclimate to chronic contaminant exposure via compensatory processes. For example, many fish, including striped bass, can detoxify metals through greater production of the metalbinding protein metallothionein (Geist et al 2007;Spearow et al 2011). Because contaminants are agents of natural selection, over multiple generations some organisms develop heritable resistance to aromatic contaminants such as polychlorinated biphenols (PCBs; electronic coolants), polycyclic aromatic hydrocarbons (PAHs; by-products of combustion) (Wirgin and Waldman 2004;Yuan et al 2006;Wirgin et al 2011), pesticides (Relyea and Hoverman 2006), and metals Guinand et al 2010).…”
Section: Conceptual Model Of Interactions Between Life Stages and Strmentioning
confidence: 99%